Contraception-Related Venous Thromboembolism in Adolescents - O'Brien, Sarah H. (Seminars in Thrombosis and Hemostasis, 2014)
Venous thromboembolism (VTE) is a rare but serious complication of combined hormonal contraception. While the absolute risk of VTE is low in adolescents, thrombotic events in contraception users younger than the age of 20 years account for 5 to 10% of total contraception-related VTE events in population studies, because of the high frequency of contraception use in adolescents. An increased risk of VTE exists not only with oral contraceptives, but also the contraceptive patch and vaginal ring. Most adolescents who experience contraception-related VTE have additional transient or inherited thrombotic risk factors at the time of VTE. Although the presence of inherited thrombophilia impacts the risk of contraception-related VTE, thrombophilia screening before contraception prescribing should be targeted only to high-risk populations. Pediatric institutions, caregivers, and young women need to be aware of the risk of VTE with estrogen-containing contraception, and maintain a high index of suspicion for this complication in women using these agents.
Keywords: deep vein thrombosis; pulmonary embolism; inherited thrombophilia; adolescents